The use of volatile organic compounds in preventing and managing invasive plant pests and pathogens - Favaro, Riccardo; Berka, Miroslav; Pettersson, Martin; Thöming, Gunda; Arce, Carla C. M.; Inácio, Maria L.; Turlings, Ted C. J.; Faria, Jorge M. S.; Jung, Thomas; Bazin, Damien; Pozzebon, Alberto; Angeli, Sergio; et al. (Frontiers in Horticulture, 2024)
Invasive pests and plant pathogens pose a significant threat to ecosystems and economies worldwide, prompting the need of anticipatory strategies. Preventing their introduction by detection at the ports of entry has been proven extremely difficult. This review explores the potential of biogenic volatile detection as a reliable preventive solution. It underscores the importance of early detection and rapid response as integral components of effective invasive pest management, and it discusses the limitations of current control measures and the increasing globalization that facilitates the spread of pests and pathogens. Through a synthesis of existing literature, this review analyzes the Volatile Organic Compound (VOC) emissions in five invasive model species: three insects, Halyomorpha halys, Spodoptera frugiperda, Helicoverpa armigera, a nematode, Bursaphelenchus xylophilus, and an oomycete, Phytophthora ramorum. The review focuses on the specific volatiles, released by both the invasive organisms and the infested host plants. If available, the volatiles emitted from similar species were considered for comparison. Ultimately, this review highlights specific pest volatile and shared Herbivore Induced Plant Volatiles (HIPVs) as a reliable and innovative solution in pest detection. If possible, candidate compounds are provided, whilst the lack of some emphasizes the urge of expanding the information available.